Development of a points-based system for determining workload for a neonatology full-time equivalent. (December 2018) - Olsen, Steven; Kilbride, Howard
Abstract Quantifying the workload for a hospital-based physician can be a challenge. We developed a novel approach to providing equity and flexibility for physicians working in a large system with heterogeneous clinical activities. In developing this points-based system, expected clinical work hours were calculated for a full-time equivalent. A point value was assigned to each clinical service based upon the hours, complexity and intensity of the work. A hypothetical work schedule was created using the expected clinical hours and translated into points needed for a full-time clinician. Faculty appreciate the flexibility and feel appropriately valued and equitably paid. Our system serves as a recruitment tool and enables the division to better understand resource needs and predict the need for additional staff. Development of a point-based model for calculating clinical work has successfully created a homogeneous system to define and measure physician work expectations in a heterogeneous clinical environment.